Chemical composition and comparison of genetic variation of commonly available Thai garlic used as food supplement - S. Sommano (2018)
© 2016 The Author(s). In order to classify true garlic cultivars, comparisons of oil composition and genetic of three garlic cultivars (Allium sativum L.) commonly used for essential oil production in the northern Thai market [viz., Thai (TH), Chinese (CH) and Pingpong (PP) cultivars] were carried out. Garlic essential oils were obtained by hydrodistillation and microwave hydrodistillation which were then analysed for chemical components by gas chromatography-mass spectrometry. The RAPD data suggests similarity (>95%) of the three cultivars in chemical compositions, and the major compounds are trisulphide, di-2-propenyl, the disulphide, di-2-propenyl, and the trisulphide, methyl 2-propenyl. Sulphur-containing compounds (Rf = 0.18-0.2) were detected by thin-layer chromatography (TLC) with ninhydrin staining reagent. The essential oil of CH from hydrodistillation and microwave hydrodistillation showed the highest alliin content. The RAPD analysis of the three garlic cultivars presents 45 fragments. A dendrogram shows genetic similarity between the garlic cultivars. The TH and the CH showed similarity value as 0.93, while the PP was classified as a different cluster. Though there was considerable similarity between the chemical and the genetic profiles of the TH and the CH, the CH demonstrated high potential as an ingredient in food supplement products due to its high alliin content.